The Online Visibility of South African Knowledge: Searching for Poverty Alleviation - Czerniewicz, Laura; Wiens, Kelsey (My University, 2013)
This paper reports on an investigation into the online visibility of work undertaken in South Africa in the field of poverty alleviation. An experiment with Google searches was undertaken, motivated by concerns about the visibility of South African research and development work, particularly in a context where social inequality is extreme and poverty such a critical issue. Aware that much attention – through research and the practice of development work – is being paid to poverty alleviation 1 , the authors set out to examine whether that work could be found easily, and what the nature of the search results would be. Significant sums of public money are invested in research, which should result in the production and dissemination of locally generated knowledge as a public good grounded in local realities. A great deal of national and international funding is also spent. Thus, research published online should inform and reflect on national and regional development practice, while contributing perspectives from the South to the global corpus of poverty research. Research to understand poverty and inform the design and targeting of poverty alleviation programmes needs to be freely available and actively shared in order for it to accumulate value. In this regard it is argued that there are exponentially beneficial linkages between research, scholarly publication and social development, which originate with local knowledge production and are amplified by the availability and discoverability of that research. Availability and discoverability add breadth and depth to the potential use, value and impact of the knowledge produced.